Bridging the Generational Gap: Innovative Arabic Speaking Instructional Models for Alpha Gen Students in Pesantren - Zulfan Syahansyah; Abdurrahman (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2026)
This research is motivated by the instructional gap between traditional Arabic curricula in pesantrens and the digital-native cognitive characteristics of Generation Alpha. The primary objective is to formulate a curriculum reconstruction and innovative teaching strategies capable of enhancing students' speaking competence through a hybrid approach. Employing a qualitative case study method, data were gathered through in-depth interviews, observations, and documentation at modern Islamic boarding schools. The findings reveal that traditional instructional models trigger high cognitive loads and linguistic barriers, particularly language anxiety, among students. However, the implementation of the "High-Tech High-Touch" strategy—utilizing virtual reality simulations and creative projects—significantly improves students' speaking confidence and engagement. The reconstruction of a user-experience-oriented curriculum effectively neutralizes the linguistic rigidity prevalent in classical methods. This study impacts the field by providing a roadmap for policymakers to transform Arabic pedagogy into a more adaptive system, ensuring pesantrens remain relevant as centers of international linguistic excellence capable of producing competitive orators in the future digital era.